An Evaluation of Lag Schedules of Reinforcement During Functional Communication Training: Effects on Varied Mand Responding and Challenging Behavior - Adami, Summer (Behav Anal Pract, 2017)
We evaluated the effects of lag schedules of reinforcement during functional communication training (FCT) on the varied use of mands and challenging behavior by two individuals diagnosed with autism. Specifically, we compared the effects of Lag 0 and Lag 1 schedules of reinforcement during FCT. The results showed that each participant exhibited increases in varied mand responding during FCT with the Lag 1 schedule of reinforcement relative to Lag 0; challenging behavior remained low during both FCT lag conditions relative to baseline. Results are discussed in terms of treatment implications relating to FCT and the potential prevention and/or mitigation of clinical relapse during challenges to treatment.